Answer:
The value of sum is 1323
Step-by-step explanation:
First of all we will find the value of n:
The value of n can be determined by the following formula:
an = a1 + (n - 1)d
where an= 113
a1= 13
d=5
Difference between the values = d=5
Now put the values n the formula:
113=13+(n-1)5
113=13+5n-5
Solve the like terms:
113=8+5n
Move constant to the L.H.S
113-8=5n
105=5n
Divide both sides by 5
21=n
Now put these values in the formula to find the sum:
Sn = n/2(a1 + an)
S21=21/2(13+113)
S21=21/2(126)
S21=21(63)
S21=1323
The value of sum is 1323....
a^3b^-4/a^2b^3a^-5 write without rational notation and move all terms to numerator
[tex]\bf ~\hspace{7em}\textit{negative exponents} \\\\ a^{-n} \implies \cfrac{1}{a^n} ~\hspace{4.5em} a^n\implies \cfrac{1}{a^{-n}} ~\hspace{4.5em} \cfrac{a^n}{a^m}\implies a^na^{-m}\implies a^{n-m} \\\\[-0.35em] \rule{34em}{0.25pt}\\\\ \cfrac{a^3b^{-4}}{a^2b^3a^{-5}}\implies \cfrac{a^3}{1}\cdot b^{-4}\cdot \cfrac{1}{a^2}\cdot \cfrac{1}{b^3}\cdot \cfrac{1}{a^{-5}}\implies a^3\cdot b^{-4}\cdot a^{-2}\cdot b^{-3}\cdot a^5 \\\\\\ a^3a^5a^{-2}b^{-4}b^{-3}\implies a^{3+5-2}b^{-4-3}\implies a^6b^{-7}[/tex]
Need The Answer Plz And Thank You!! I’m Failing
Angle BCA
Step-by-step explanation:
You can see this due to the angle having the name amount of congruent angle marks.
Which represents a perfect cube?
8.8.8
8+8+8
9.9.9.9
9+9+9+9+9
Answer:
8.8.8.
Step-by-step explanation:
8.8.8 = 8^3 = 512 Perfect cube.
8+8+8 =24
9.9.9.9 = 6561
9+9+9+9+9 = 45.
None of the others are perfect cubes.
Answer:A 8.8.8
Step-by-step explanation:i did the quiz
How do you do number 1?
Whenever I tried to answer it, I always get fraction. help me.
Answer:
The pairs are (13,15) and (-15,-13).
Step-by-step explanation:
If n is an odd integer, the very next odd integer will be n+2.
n+1 is even (so we aren't using this number)
The sum of the squares of (n) and (n+2) is 394.
This means
(n)^2+(n+2)^2=394
n^2+(n+2)(n+2)=394
n^2+n^2+4n+4=394 since (a+b)(a+b)=a^2+2ab+b^2
Combine like terms:
2n^2+4n+4=394
Subtract 394 on both sides:
2n^2+4n-390=0
Divide both sides by 2:
n^2+2n-195=0
Now we need to find two numbers that multiply to be -195 and add up to be 2.
15 and -13 since 15(-13)=-195 and 15+(-13)=2
So the factored form is
(n+15)(n-13)=0
This means we have n+15=0 and n-13=0 to solve.
n+15=0
Subtract 15 on both sides:
n=-15
n-13=0
Add 13 on both sides:
n=13
So if n=13 , then n+2=15.
If n=-15, then n+2=-13.
Let's check both results
(n,n+2)=(13,15)
13^2+15^2=169+225=394. So (13,15) looks good!
(n,n+2)=(-15,-13)
(-15)^2+(-13)^2=225+169=394. So (-15,-13) looks good!
Use the graph of f(x) to evaluate the following:
The average rate of change of f from x=0 to x=4 is_____.
Give your answer as an integer or reduced fraction
Answer:
-5/4
Step-by-step explanation:
The average rate of change of f from x=0 to x=4 is_____.
This means we are being asked to evaluate [tex]\frac{f(4)-f(0)}{4-0}[/tex].
To do this we will need to find f(0) and f(4).
f(0) means what y-coordinate corresponds to x=0 on the curve. Find x=0, the curve is above there, go straight up and see y=5 there. This means f(0)=5.
f(4) means what y-coordinate corresponds to x=4 on the curve. Find x=4, then curve is above there, go straight up and see y=0 there. This means f(4)=0.
So we have:
[tex]\frac{f(4)-f(0)}{4-0}=\frac{0-5}{4-0}=\frac{-5}{4}[/tex].
F(x)=x^2+3x+2 is shifted 2 units left.the result is g(x). What is g(x)?
Answer:
Either A or B.
Step-by-step explanation:
When shifting to the left you are adding to x.
Example: x^2 shifted to the left by 3. (x+3)^2
For this case we have that, by definition of horizontal translation of functions we have to:
We assume h> 0:
To graph[tex]y = f (x-h),[/tex] the graph moves, h units to the right.
To graph[tex]y = f (x + h)[/tex], the graph moves, h units to the left.
If we have the following function:
[tex]f (x) = x ^ 2 + 3x + 2[/tex]and move 2 units to the left, then:
[tex]f (x + 2) = g (x) = (x + 2) ^ 2 + 3 (x + 2) +2[/tex]
ANswer:
Option B
in 135 space shuttle missions, there were two failures. Based on these data, what's the probability of a successful mission?
Answer:
98.518 repeating prercent
Step-by-step explanation:
2 out of 135 can also be written as 2/135
2 divided by 135 is 0.014814814814
that number is the percentage of failures
100% in decimal form is 1.00
1.00 subtracted by the percentage of failures is the percentage of successes
which is .98518518518, 518 repeating move the decimal over 2 and you got the percentage 98.518 repeating
What is the midpoint of the segment shown below?
Answer:
A
Step-by-step explanation:
Calculate the midpoint using the midpoint formula
[ 0.5(x₁ + x₂ ), 0.5(y₁ + y₂ ) ]
with (x₁, y₁ ) = (- 1, 5) and (x₂, y₂ ) = (5, 5)
midpoint = [ 0.5(- 1 + 5), 0.5(5 + 5) ]
= [ 0.5(4), 0.5(10) ] = (2, 5 ) → A
Answer:
The answer would be A 2,5
Step-by-step explanation:
Find the value of x.
A. 1.1
B. 6.6
C. 8.8
D. 5.5
Answer:
B. 6.6Step-by-step explanation:
AC is a midsegment of the trapezoid DFBE.
The formula of a midsegment of trapezoid is:
[tex]m=\dfrac{a+b}{2}[/tex]
a, b - bases of a triangle
We have
a = x, b = 4.4, m = 5.5
Substitute:
[tex]5.5=\dfrac{x+4.4}{2}[/tex] multiply both sides by 2
[tex]11=x+4.4[/tex] subtract 4.4 from both sides
[tex]6.6=x\to x=6.6[/tex]
[tex] - 3 + 5i \div - 3 - 4i[/tex]
Answer:
[tex]\frac{-11}{25}+\frac{-27}{25}i[/tex] given you are asked to simplify
[tex]\frac{-3+5i}{-3-4i}[/tex]
Step-by-step explanation:
You have to multiply the numerator and denominator by the denominator's conjugate.
The conjugate of a+bi is a-bi.
When you multiply conjugates, you just have to multiply first and last.
(a+bi)(a-bi)
a^2-abi+abi-b^2i^2
a^2+0 -b^2(-1)
a^2+-b^2(-1)
a^2+b^2
See no need to use the whole foil method; the middle terms cancel.
So we are multiplying top and bottom of your fraction by (-3+4i):
[tex]\frac{-3+5i}{-3-4i} \cdot \frac{-3+4i}{-3+4i}=\frac{(-3+5i)(-3-4i)}{(-3-4i)(-3+4i)}[/tex]
So you will have to use the complete foil method for the numerator. Let's do that:
(-3+5i)(-3+4i)
First: (-3)(-3)=9
Outer:: (-3)(4i)=-12i
Inner: (5i)(-3)=-15i
Last: (5i)(4i)=20i^2=20(-1)=-20
--------------------------------------------Combine like terms:
9-20-12i-15i
Simplify:
-11-27i
Now the bottom (-3-4i)(-3+4i):
F(OI)L (we are skipping OI)
First:-3(-3)=9
Last: -4i(4i)=-16i^2=-16(-1)=16
---------------------------------------------Combine like terms:
9+16=25
So our answer is [tex]\frac{-11-27i}{25}{/tex] unless you want to seprate the fraction too:
[tex]\frac{-11}{25}+\frac{-27}{25}i[/tex]
Which properties of equality are used to solve the following (in no particular order)?
3(x + 12) - 2 = 50
Addition Property of Equality
Subtraction Property of Equality
Division Property of Equality
Combine Like Terms
Distributive Property
All except combine like terms. Since you only have 1 variable.
Hope this helps.
r3t40
How to solve this 336+x/5=85
Answer:
x = -1255
Step-by-step explanation:
336+x/5=85
Subtract 336 from each side
336-336 +x/5=85-336
x/5 =-251
Multiply each side by 5
x/5 * 5 = -251 *5
x = -1255
A triangle has vertex A at (0, 0), vertex B at (2, 5), and vertex C at 1
(4, 5). Which side of the triangle has the greatest slope?
0
Check the picture below.
I would like to check my answer! Have I done this correctly ? :)
Answer:
Yes you are right.
The answer is .45 or 45/100 which reduces to 9/20.
Step-by-step explanation:
[tex]\frac{4x}{15}=\frac{3}{25}[/tex]
Your first step is to cross multiply:
[tex]15(3)=25(4x)[/tex]
Simplify both sides:
[tex]45=100x[/tex] You got this! You go!
Divide both sides by 100:
[tex]\frac{45}{100}=x[/tex]
You wrote 45/100 as .45 which is correct!
Nice.
What is 7(x+6)=3(x+9)
Answer:
x= -3.75
Step-by-step explanation:
Answer:
x = -15/4
Step-by-step explanation:
7(x+6)=3(x+9)
Distribute
7x+42 = 3x+27
Subtract 3x from each side
7x-3x+42 = 3x-3x+27
4x +42 = 27
Subtract 42 from each side
4x+42-42 = 27-42
4x =-15
Divide each side by 4
4x/4 =-15/4
x = -15/4
When solving -1/5 (x − 25) = 7, what is the correct sequence of operations?
A:Multiply each side by negative one over five , add 25 to each side
B:Multiply each side by 5, subtract 25 from each side
C:Multiply each side by negative one over five , subtract 25 from each side
D;Multiply each side by −5, add 25 to each side
Answer:
It is C. Multiply each side by negative one over five , subtract 25 from each side.
Hope this helped you! :3
Answer:
D;Multiply each side by −5, add 25 to each side
Step-by-step explanation:
-1/5 (x − 25) = 7
To solve this equation, we will first multiply both-side of the equation by -5
-5 × -1/5(x-25) =7 × 5
(At the left-hand side of this equation, the 5 we multiplied will cancel the 5 at the denominator, leaving us with just '1' since negative multiply by negative is positive), Hence our equation becomes;
(x - 25) = 35
x - 25 = 35
Then the next thing to do is to add 25 to both-side of the equation in other to get the value of your x
x -25 + 25 = 35 + 25
x=60
Therefore, option D is the correct sequence of operation to follow to enable you solve the equation.
Which graph represents the solution set of the inequality x+2 greater than or equal to 6
Answer:
4 ≤ x
4
●→
Step-by-step explanation:
There is no illustration, it looks something like this.
Which one of the following equations could describe the graph above?
Answer: A. y=(1/2)^x+6
Step-by-step explanation: If this is the graph you’re talking about-
When “a” is less than one, the graph increases exponentially to the left. The smaller the value of a, the steeper the slope of the line.
There is a vertical shift up 6 as well
Three terms of an arithmetic sequence are shown below. Which recursive formula defines the sequence? f(1) = 6, f(4) = 12, f(7) = 18 f (n + 1) = f(n) + 6 f (n + 1) = 2f(n) f (n + 1) = f(n) + 2 f (n + 1) = 1.5f(n)
Answer:
f(n + 1) = f(n) + 2
Step-by-step explanation:
A recursive formula gives any term in the sequence from the previous term.
the n th term of an arithmetic sequence is
f(n) = f(1) + (n - 1)d ← d is the common difference
Given
f(1) = 6 and
f(4) = 12, then
f(1) + 3d = 12, that is
6 + 3d = 12 ( subtract 6 from both sides )
3d = 6 ( divide both sides by 3 )
d = 2
To obtain a term in the sequence add 2 to the previous term, hence
f(n + 1) = f(n) + 2 ← recursive formula
Answer:
c
Step-by-step explanation:
its c
factor: d2 + 16dm + 64m2
Answer:
[tex](d + 8m)^2[/tex]
Step-by-step explanation:
[tex]d^2 + 16dm + 64 m^2 = (d + 8m)^2[/tex]
d^2 + 16dm + 64m^2
64m^2 + 16dm + d^2
Note: This polynomial is already in lowest terms. It cannot be factored. Are you sure that you posted the entire, correct problem?
If Sn=n^2+3 then t10=?
Answer:
T10= -21
Step-by-step explanation:
If Sn=n^2+3 then t10=?
Sn= n²+5
put n=1, 2
S1= T1 = (1)²+5
=1+5 =6
S2= n²+5
S2=(2)²+5
S2=4+5
S2=9
T2 = S2 - S1
T2 = 9-6
T2=3
T10 = a+(n-1)d
where a = 6, d = -3, n=10
T10= 6+(10-1)*-3
T10=6+(9)*-3
T10=6+(-27)
T10=6-27
T10= -21
Therefore T10= -21 ....
for the level 3 course, examination hours cost twice as much as workshop hours and workshop hours cost twice as much as lecture hours. how id the lectures cost per hour? Total cost level 3 =$528
Answer:
The lectures cost is $7.33 per hour
Step-by-step explanation:
* Lets explain how to solve the problem
- For the level 3 course the examination hours cost twice as much
as workshop hours
- The workshop hours cost twice as much as lecture hours
- There are examination hours , workshop hours and lecture hours
- There are 3 hr for examination, 24 hr for workshops and 12 hr
for lectures
* Let the cost of the lecture hours is $x per hour
∴ The cost of the lecture hours is x per hour
∵ The cost of workshop hours is twice the cost of lecture hours
∴ The cost of the workshop hours is 2(x) = 2x per hour
∵ The cost of examination hours is twice the cost of workshop hours
∵ The cost of the workshop hours is 2x
∴ The cost of examination hours is 2(2x) = 4x per hour
- The cost of the level 3 is the sum of the costs of the lecture hours,
workshop hours and examination hours
∵ There is 12 hours for lectures
∵ There is 24 hours for workshops
∵ There is 3 hours for examination
∵ The total cost of level 3 = 12(x) + 24(2x) + 3(4x)
∴ The total cost of level 3 = 12 x + 48 x + 12 x
∵ The total cost of level 3 = $528
∴ 12 x + 48 x + 12 x = 528
∴ 72 x = 528 ⇒ divide both sides by 72
∴ x = 7.33
∵ x is the cost of the lecture hours per hour
∴ The lectures cost is $7.33 per hour
HELPPPP WILL NAME BRAINIEST
Answer:
Triangle APB is an isosceles triangle ⇒ 3rd answer
Step-by-step explanation:
* Lets explain the how to solve the problem
- ABCD is a square
∴ AB = BC = CD = AD
∴ m∠A = m∠∠B = m∠C = m∠D = 90°
- DPC is equilateral triangle
∴ DP = PC = DC
∴ m∠DPC = m∠PCD = m∠CDP = 60°
- In the Δs APD , BPC
∵ AD = BC ⇒ sides of the square
∵ PD = PC ⇒ sides of equilateral triangle
∵ m∠ADB = m∠BCP = 30° (90° - 60° = 30) ⇒ including angles
∴ Δs APD , BPC are congregant ⇒ SAS
- From congruent
∴ AP = BP
∴ Triangle APB is an isosceles triangle
Two tins are geometrically similar. If the ratio of their volume is 27:64 find the ratio of their curved surface area.
Answer:
9 : 16
Step-by-step explanation:
Given 2 similar figures with linear ratio = a : b, then
area ratio = a² : b² and
volume ratio = a³ : b³
Here the volume ratio = 27 : 64, hence
linear ratio = [tex]\sqrt[3]{27}[/tex] : [tex]\sqrt[3]{64}[/tex] = 3 : 4
Hence area ratio = 3² : 4² = 9 : 16
In a certain card game you draw one card off a standard deck of 52 cards. If you draw a spade you get paid $12, if you draw a red Ace you get paid $20, and if you draw a red Queen you get paid $38. If you draw anything else, you get paid nothing. What should this game cost if it is to be a fair game? Use fractions in your work and then calculate the answer as a decimal rounded to 4 decimal places.
Step-by-step explanation:
In a standard deck of 52 cards, there are 2 red aces, 2 red Queens, and 13 spades. That leaves 35 cards for everything else.
For the game to be fair, the cost must equal the expected value. The expected value is the sum of each outcome times its probability.
C = (12) (13/52) + (20) (2/52) + (38) (2/52) + (0) (35/52)
C = 68/13
C ≈ 5.2308
The digits of a two-digit number sum to 8. When the digits are reversed, the resulting number is 18 less than the original
number. What is the original number?
Answer:
It's 53.
Step-by-step explanation:
Let the number be xy so the digits are x and y, so:
x + y = 8...........(1)
Reversing the 2 digits we have the number 10y + x and this equals
10x + y - 18 so we have the equation:-
10x + y - 18 = 10y + x
9x - 9y = 18
x - y = 2...........(2) Adding equations (1) and (2) we have:
2x = 10
x = 5
and y = 8 - 5 = 3.
So the original number is 53.
We can check this as follows
Original number is 53 so the reverse is 35 .
53 - 35 = 18 which checks out.
Here's another coaster that will help you think about the effect of a factor's exponent!
Once again, make the coaster cross at x = 500 after an initial rise and fall.
• This time, make your track more realistic: make the coaster come in smoothly at x = 1000 instead
of just falling and suddenly stopping!
y = Flax(x – 1000)
Answer: y=-ax(x-500)(x-1000)^2
Step-by-step explanation:
The behavior of the x-intercept of a graph is given by the multiplicity of the zero
The required polynomial for the coaster is, y = -a·x·(x - 500)·(x - 1000)²
Reason:
The question relates to the introduction of characteristics to the graph of a polynomial through knowledge of the effect of parameters of a polynomial
Known parameter:
Parent function is, y = a·x·(x - 1000)
The polynomial crosses the x-axis when (x - 500) is a factor of the polynomial, therefore, we have;
y = a·x·(x - 500)·(x - 1000)
Given that the graph is to initially rise, the leading coefficient is negative, therefore, we have;
y = -a·x·(x - 500)·(x - 1000)
For the polynomial to come in smoothly to stop at y = 0, when x = 1,000 we have that a turning point of the polynomial will be located at x = 1,000, this is given by introduction of a bump on the x-axis at x = 1,000 with a factor of (x - 1,000)²
Therefore, the required polynomial is y = -a·x·(x - 500)·(x - 1000)²
The height of the above polynomial is progressively smaller as x tends towards 1,000, given that the factors, (x - 500), and (x - 1,000), becomes smaller.
Learn more about the graph of polynomial functions here:
https://brainly.com/question/11829982
What is the greatest common factor of 8x and 40y
Answer:
The GCF of both the terms is 8....
Step-by-step explanation:
Given:
What is the greatest common factor of 8x and 40y.
The GCF of 8x and 40y is 8.
We will use the method of prime factorization to find the greatest common factor.
The prime factorization of 8x is:
8x = 2*2*2*x
The prime factorization of 40y is:
40y = 2*2*2*5*y
Therefore the common factors in both the terms are 2*2*2 which becomes 8
Thus the GCF of both the terms is 8....
Answer:
8
Step-by-step explanation:
Events A and B are disjointed.
P(A) = 4/11 ; P(B) = 3/11.
Find P(A or B).
*Answer Options*
7/11
4/11
3/11
8/11
Answer:
7/11
Step-by-step explanation:
Two events are disjoint events if they cannot occur at the same time. It is given that A and B are disjointed events, so A and B cannot occur at the same time i.e. the intersection of two disjoint events will be 0.
For two disjoint events A and B:
P(A or B) = P(A) + P(B)
P(A) is given to be 4/11 and P(B) is given to be 3/11. Using these values in the equation, we get:
P(A or B) = [tex]\frac{4}{11}+\frac{3}{11} = \frac{3+4}{11}=\frac{7}{11}[/tex]
A group of students and workers entering a metro station
were asked whether they were riding the bus or the
subway. The two-way table shows their answers.
Types of Transportation
Bus
Subway
Students
Workers
Total
166
27 + 42 + 21 + 76 = 166